2003
DOI: 10.1097/00007691-200304000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Mofetil for Solid Organ Transplantation: Does the Evidence Support the Need for Clinical Pharmacokinetic Monitoring?

Abstract: The need for clinical pharmacokinetic monitoring (CPM) of the immunosuppressant mycophenolate mofetil (MMF) has been debated. Using a previously developed algorithm, the authors reviewed the evidence to support or refute the utility of CPM of MMF. First, MMF has proven efficacy for prevention of organ rejection in renal and cardiac transplant populations. In addition, the pharmacologically active form of MMF, mycophenolic acid (MPA), can be measured readily in plasma, and relationships between the incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 91 publications
(142 reference statements)
3
71
0
2
Order By: Relevance
“…The target C2 level in the first 2 months is 1700-2100 ng/mL. A 12-h MPA AUC (AUC [0][1][2][3][4][5][6][7][8][9][10][11][12] …”
Section: Pharmacokinetic Analysis and Laboratory Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The target C2 level in the first 2 months is 1700-2100 ng/mL. A 12-h MPA AUC (AUC [0][1][2][3][4][5][6][7][8][9][10][11][12] …”
Section: Pharmacokinetic Analysis and Laboratory Methodsmentioning
confidence: 99%
“…Mycophenolate mofetil (MMF) has become standard therapy with microemulsion cyclosporine (Neoral) or tacrolimus. Several studies have found associations of mycophenolic acid (MPA, the active metabolite) exposure with both efficacy and toxicity (5)(6)(7)(8)(9). After an analysis of the studies, a consensus group has proposed a therapeutic window for MPA (30-60 mg * h/L) (8).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Furthermore, early after transplant, high variations between patients in AUC has been documented. 11,12 Therefore, therapeutic drug monitoring of MMF is recommended early after transplant. 13 The main purpose of this study was to determine the MPA pharmacokinetic profile early after transplant in Iranian kidney graft recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Several publications have recommended individualization of MMF therapy based on plasma concentration measurements because of (1) large variability in the pharmacokinetics of mycophenolic acid (MPA), the active metabolite of MMF in patients; (2) time-dependent changes in the pharmacokinetics of MPA within patients; (3) lack of a correlation between dose and plasma MPA concentrations; (4) variability in the MPA concentration / pharmacokinetics based on coadministered immunosuppressive drugs; (5) a decrease in the incidence of rejection with an increase in area under the plasma concentration vs. time curve (AUC) of MPA, and to a lesser extent with predose trough plasma MPA concentrations; (6) increased incidence of side effects in patients with higher AUC of MPA; (7) a relationship between MPA concentration and activity as measured by suppression of DNA synthesis or expression of T cell activation markers, in vitro; (8) difficulty in assessing the clinical response to MMF therapy; (9) narrow therapeutic index of MPA; and (10) the significant consequences of therapeutic failure (rejection). [1][2][3][4][5] Most of the studies published to date have been carried out in renal and cardiac transplant patients.…”
mentioning
confidence: 99%
“…(2) What is the therapeutic range to be achieved when MMF is used alone versus when it is used in combination with other agents? (3) What is the optimal therapeutic range for MPA early after transplantation compared with a later time after transplantation? (4) Does the trough MPA level provide a proper estimate of drug exposure, especially when it is more sensitive to enterohepatic recycling?…”
mentioning
confidence: 99%